UZBEK LITERATURE - Kenjaboyeva Feruzaxon Baxtiyorovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. Uzbek literature is a rich tapestry woven from the historical, cultural and social fabrics of Uzbekistan. This article explores the evolution of Uzbek literature, exploring its roots, key figures and important works. It explores the literary movements that shaped it and the contemporary trends that continue to influence it. The study uses a combination of historical and literary analysis to provide complete information from the origins of Uzbek literature to the present day.